2021
DOI: 10.3390/agronomy11112295
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Varieties of Mountain Maize: The Inheritance of the Pointed Character and Its Effect on the Natural Drying Process

Abstract: The introduction of mechanized agricultural practices after the Second World War and the use of productive hybrids led to a gradual disappearance of local maize varieties. However, 13 landraces are still cultivated in North-Western Italy, in the Lombardy region; those that are cultivated in mountainous areas (roughly up to 1200 m in altitude) are often characterized by the pointed shape of their seeds (i.e., “Nero Spinoso”, “Rostrato Rosso di Rovetta”, “Spinato di Gandino” and “Scagliolo di Carenno”) and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Interestingly, only the landrace Perloz can be classified in the group of “Rostrata” having pointed-beaked kernels. This particular trait is very common in mountain maize landraces since it is associated to better drying and storage ability of the kernels [ 4 ]. Intra-population variability was noticed for characters that are not considered by farmers for selection, i.e., tassel traits, while farmers’ relevant traits as ear shape and color appear to be uniform or fixed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, only the landrace Perloz can be classified in the group of “Rostrata” having pointed-beaked kernels. This particular trait is very common in mountain maize landraces since it is associated to better drying and storage ability of the kernels [ 4 ]. Intra-population variability was noticed for characters that are not considered by farmers for selection, i.e., tassel traits, while farmers’ relevant traits as ear shape and color appear to be uniform or fixed.…”
Section: Resultsmentioning
confidence: 99%
“…From that moment, its cultivation began to grow more and more leading in the centuries to the selection of local varieties (landraces) perfectly adapted to the different microclimatic areas of the Italian territory [ 2 , 3 ]. Landraces are defined as dynamic populations of genetically diverse individuals well adapted to local conditions, associated with traditional agricultural practices and local history; moreover, they can be considered the ultimate expression of crop domestication [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of biodiversity has been a crucial problem in the last century, and it was estimated that about 75% of the species of living things used for food and agriculture were lost; nowadays, three-quarters of global food produced is composed of only five animal species and twelve plant species [1][2][3][4][5]. Thus, the safeguarding and the promotion of agrobiodiversity have been central issues in recent decades [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of tolerant genotypes could potentially reduce the reliance on chemical inputs. Also, many authors reported that the use of genotypes with pigmented pericarp appears promising for mitigating Fusarium infection (Landoni et al, 2020;Pilu et al, 2011;Sangiorgio et al, 2021;Venturini et al, 2016). Considering maize morphology, husk leaves have a significant impact on the susceptibility of maize to Fusarium.…”
Section: Discussionmentioning
confidence: 99%